INDONESIAN TRADITIONAL GAME «BANDHUL SADA» IN LEARNING ROTATION DYNAMIC CONCEPTS WITH CONTEXTUAL APPROACH - Fatmaryanti, Siska Desy (Physical and Mathematical Education, 2023)
Teachers can support cultural preservation while also providing a relevant and interesting way to teaching diverse subjects by including traditional games into the learning process. The aim of this research is identify the rotation dynamic concepts of Indonesian traditional game «Bandhul Sada» with contextual approach Formulation of the problem. We focused how to learn the rotational dynamic concept with traditional game «Bandhul Sada» and implementation learning steps with contextual approach.This identification includes analysis of rotation dynamic consepts in “Bandhul Sada” and analysis of learning steps with a contextual approach to the application of the game. Materials and methods. The method used qualitative approach with descriptive analysis. In the analysis of rotation dynamic concepts and learning step in contextual approach, we used the method of narrative review research. Literature and observation have been used as the data collection methods. In the analysis of learning step, we used the literature review includes gathering information through literature that supports the development of learning steps based on a contextual approach. Results. Result of the research shows that (1) in «Bandhul Sada» game can be explained the concept of rotation dynamics that occur, namely linear speed, angular velocity, and angular momentum; (2) this game can be applicate in learning with contextual approach. This learning consist of 5 phase. There were constructing knowledge possessed by students, developing students’ initial knowledge, using game «Bandhul Sada» in delivering material concepts, conducting inquiry processes through discussion activities and finally reflection. From all these learning phases, it appears that there is a relationship between teaching approaches and achievement of goals. Conclusions. Thus it can be concluded that the traditional game «Bandhul Sada» can be used as a real example in learning physics the concept of rotational dynamics such as angular velocity and linear velocity. And it provides students with valuable experience in constructing their own knowledge in a variety of methods.